INTEGRASI MUSIK DALAM PENDIDIKAN SOSIAL CARA BARU UNTUK MENINGKATKAN EMPATI DAN KESADARAN SOSIAL - Rasimin; MS Viktor Purhanudin; Rifky Fandanu; Baroroh Barir; Al Ikhlas; Ali Ramatni (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Social education plays an important role in shaping individuals who care about the social environment and humanity. However, conventional approaches often lack the ability to capture students' attention and build deep emotional engagement. This research explores the potential of music integration as an innovative tool in social education to enhance empathy and social awareness. Music has the unique ability to bridge cultural differences, stimulate emotions, and encourage deep reflection on social issues. In this study, qualitative methods were used to analyze the impact of music on students' understanding of social themes, such as social justice, diversity and solidarity. The study involved observations, interviews, and analysis of the experiences of students who participated in music-based learning programs in several secondary schools. The results showed that music not only enriched the learning process, but also significantly improved students' ability to feel empathy for others and understand complex social issues. Thus, music integration in social education can be a transformative approach to creating a more socially sensitive, caring and responsible generation.